Changes in the transcriptional activity of cell cycle regulator CDK1 and cell proliferation ki67 genes in invasive and non-invasive pancreatic ductal adenocarcinoma - A. V. Evseyev; A. M. Kamyshnyi (Zaporozhye State Medical University, 2016)
The aim of this work was to determine the levels of mRNA expression of CDK1 and ki67 in pancreatic ductal adenocarcinoma. Materials and methods. The study was conducted on 20 samples of pancreatic tumor tissue taken at pathomorphological examination of the operational material. To determine the level of investigated genes expression a thermal cycler CFX96 ™ Real-Time PCR Detection Systems («Bio-Rad Laboratories, Inc.», USA) reagent kit and Maxima SYBR Green / ROX qPCR MasterMix (2X) (ThermoScientific, USA) were used. In work using the real time polymerase chain reaction, gene expression levels of CDK1 and ki67 in noninvasive and invasive ductal pancreatic adenocarcinoma cells were identified. Results. As a result of the study it was found that in ductal carcinoma tissue there is an increase of mRNA levels of the studied genes. Thus there was a significant increase in ki67 mRNA level (from 14.26 to 251.97 times) and increased CDK1 mRNA (from 0.26 to 10.73 times) as compared to normal pancreatic tissue. Conclusion. Correlation analysis showed that between the growth of the transcriptional activity of cell cycle regulator CDK1 and cell proliferation Ki67 genes there is a strong direct correlation (Pearson's correlation coefficient r=+0,70), that is, increase of the level of CDK1 mRNA is accompanied by the significant increase in levels of ki67 mRNA, resulting in the enhance of tumor cell proliferation index. Unidirectional dynamics of increasing transcriptional activity of both genes was shown (ki67 increased by 54,40±23,82 times in non-invasive and 159,24±66,25 times in invasive carcinoma; CDK1 increased by 2,10±1,47 and 4,16±4,04 times, respectively) with a strong correlation between these two indicators (Pearson's coefficient r=+0,74 and +0,75, respectively). Invasive pancreatic carcinoma as compared to adenocarcinoma without invasion is characterized by the significant increase in the mRNA levels of both genes, however, this difference is valid only for the cell proliferation ki67 gene.